Transforming Hate into Compassion as an Islamic Nonviolent Thought of Bediüzzaman Said Nursi - Ziaulhaq, Mochamad; Sen, Hasbi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
The study of hatred that emerges as human nature can provide an analytical picture of how hatred arises, develops, and turns into humanitarian incidents. With an in-depth, systematic, and genealogical study, it can come up with a panacea for this hatred. The elixir can turn hatred into compassion, violence into nonviolence, and find creative ways to turn conflict into peace; thus, creating a new, better reality. This qualitative research uses a literature study from Risale-i Nur by Bediüzzaman Said Nursi (1877-1960). In this study, Nursi's religious and psychological explanations are compared with religious theories and studies of peace and conflict that are already popular in the Western world. The data in Risale-i Nur were analysed using the Mimesis theoretical framework of the philosophical approach. With this analysis there is the prefiguration stage (Mimesis I) about the background of Said Nursi's life, the configuration stage (Mimesis II) about the story of Said Nursi's traumatic experience, and the transfiguration stage about the emergence of the capacity to handle conflict independently with others using nonviolent ideas creatively, thus creating a new reality (Mimesis III). This new reality is "nonviolent Islam," which transforms conflict nonviolently, overcoming hatred with compassion and forgiveness. This statement is based on the argument that hatred is the root of violence, and Said Nursi can escape the trap of hatred through compassion and forgiveness. This study can contribute ideas to the study of moral philosophy and can also be used as a reference for training modules and sharing experiences to reduce conflict in society or between communities.